Aqueous urea solution destabilizes Aβ(16–22) oligomers - Klimov, D. K. (National Academy of Sciences, 2004)
We use long multiple trajectories generated by molecular dynamics simulations to probe the stability of oligomers of Aβ(16–22) (KLVFFAE) peptides in aqueous urea solution. High concentration of urea promotes the formation of β-strand structures in Aβ(16–22) monomers, whereas in water they adopt largely compact random coil structures. The tripeptide system, which forms stable antiparallel β-sheet structure in water, is destabilized in urea solution. The enhancement of β-strand content in the monomers and the disruption of oligomeric structure occur largely by direct interaction of urea with the peptide backbone. Our simulations suggest that the oligomer unbinding dynamics is determined by two opposing effects, namely, by the increased propensity of monomers to form β-strands and the rapid disruption of the oligomers. The qualitative conclusions are affirmed by using two urea models. Because the proposed destabilization mechanism depends largely on hydrogen bond formation between urea and the peptide backbone, we predict that high urea concentration will destabilize oligomers of other amyloidogenic peptides as well.